Rimboschimenti della Presila di Cosenza: tre conifere a confronto - Bernardini, Vincenzo; Clerici, Erica (Annals of Silvicultural Research, 2026)
Reforestation of Presila di Cosenza: three conifers compared. A comparison was made between forestations of Atlas cedar, Douglas fir and Calabrian pine realized in the mid-70s of the last century with identical modalities and in the same station conditions, in the Presila of Cosenza. The results achieved by the plantations must be considered, according to their main aim that was concerned with the fulfilments of essentially protective tasks, definitely positive. The data relating the rates of take and mortality through the years confirm the great ability to colonise and to form thick and pure crops on behalf of the calabrian pine, while the incremental ones emphasise the Douglas fir as a species with a quicker growth. The densities does not allow, in the test areas, the regeneration to assert itself. Surveyings on the phytosanitary state of the forest stands do not evidence, in the test areas, symptoms of suffering, while the margin plants in the warm slopes of the pine-wood strongly turn out exposed to the processionary attacks. The more important requirement, for the investigated crops, is represented by the carrying-out of silvicultural cuttings, which aim at: regulating their thickness and structure, increasing their biological stability, creating favourable conditions for their renaturalization.